ANALISA KETERLAMBATAN PROSES PELAYANAN UNIT LAUNDRY DI RUMAH SAKIT BALIMED KARANGASEM - Wirama, I Putu (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2022)
Laundry units in hospitals have an essential role in breaking the transmission chain of infection to staff and patients, especially during the COVID-19 pandemic. From the observation of the management team, the laundry service at BaliMed Karangasem Hospital needs to be revised. It can be seen from the timely provision of linen and incidents of lost linen, even though interventions have been carried out. Management has yet to realize the process in the laundry unit that depends on the machine, so the machine maintenance process has not been carried out correctly and on schedule. In addition, evaluating service processes has yet to be routinely carried out. Hospitals are complex industries that must continually evaluate and improve service processes to ensure quality and efficiency go hand in hand. This research is qualitative research with a case study to evaluate the delay in the service process in the laundry unit. Brainstorming is carried out with all officers in the laundry unit, which is then depicted in a fishbone diagram. The results of the research include that hospital management must consider two main things: machine maintenance and re-evaluation of service processes. In addition, the process of monitoring and evaluating the implementation of the service process must always be carried out.